Collision course? Donald Trump, Paul Ryan, and the fate of Medicare. Issue 3 (8th August 2018) - Oberlander, Jonathan
ABSTRACT: The election of Donald Trump as president of the United States raises questions about the future of Medicare. How will Medicare fare under Republican-led government? There are several compelling reasons that the Trump administration and Congressional Republicans might avoid Medicare reform, including the political risks of taking on a popular program, the difficulties the party has encountered in trying to dismantle the Patient Protection and Affordable Care Act (ACA), the importance of older Americans to the GOP coalition, and President Trump's views about Medicare. However, because of fiscal pressures and the commitment of Speaker of the House Paul Ryan and other Republicans to entitlement reform, the GOP nonetheless could end up attempting to make major changes in Medicare. Alternatively, Republican efforts to repeal and undermine the ACA could unintentionally enhance the political fortunes of proposals to expand Medicare. Consequently, the fate of Medicare during the Trump administration remains highly uncertain.